Kalimat imperatif dalam Bahasa Bengkulu di akun tiktok @roykiosaki_ : Kajian sintaksis - Amanda, Putri; Bhrata, Pramudya Dhana; Winarni, Efid; Sumarlam, Sumarlam (Aksara: Jurnal Bahasa dan Sastra, 2024)
This research aims to classify the use of imperative sentences in Bengkulu on the TikTok account @roykiosaki_ through syntax studies. This research study uses a qualitative descriptive method. Therefore, this research specifically analyzes the imperative sentences used by one of the content creators on the TikTok platform. The data in this research is in the form of speech or conversation (dialogue) between characters in which there are imperative sentences and their context. The data source in this research is the TikTok video account @roykiosaki_. Data was collected using the listening method and note-taking techniques with orthographic transcription. Data was obtained from speech/conversation (dialogue) between characters played personally in which there were imperative sentences and their context. Data collection techniques used include Cakap Free Involvement Listening (SBLC) techniques, note-taking techniques and content analysis. The data analysis technique uses the distribution method as well as the loss technique and replacement technique as advanced techniques. This research includes an analysis of imperative sentences in the Bengkulu regional language on the TikTok social media account @roykiosaki_ based on syntactic studies, namely involving intonation and imperative sentences as well as language markers which can result in differences in the way they are delivered but have the same meaning, namely commanding sentences. The results of this research concluded that there were 46 data each, 26 ordinary imperative sentences, 2 soft imperative sentences, 2 request imperative sentences, and 16 prohibition imperative sentences in the TikTok video content @roykiosaki_, no invitation imperative sentences were identified. The particle markers "-lah" and "-kan" in Bengkulu are most commonly used in ordinary imperative sentences and prohibitions. Of the several words that indicate imperative sentences, they can be deleted or replaced (substituted) using the technique for direct elements (BUL), but there are also words that cannot be deleted or replaced because they will change the meaning or are even unacceptable/meaningless at all. Keywords: Imperative Sentences, Bengkulu, Intonation, Lingual Markers, Social Media